The Characteristics of White Matter Hyperintensities in Patients With Migraine - Chong, Catherine D.; Schwedt, Todd J.; Trivedi, Meesha; Chong, Brian W. (Frontiers in Pain Research, 2022)
Background: The presence of white matter hyperintensities (WMH) in migraine is well-documented, but the location of WMH in patients with migraine are insufficiently researched. This study assessed WMH in patients with migraine using a modified version of the Scheltens visual rating scale, a semiquantitative scale for categorizing WMH in periventricular, lobar, basal ganglia, and infratentorial regions. Methods: 263 patients with migraine (31 male/232 female) enrolled into the American Registry for Migraine Research (ARMR) from Mayo Clinic Arizona and who had clinical brain magnetic resonance imaging (MRI) were included in this study. Those with imaging evidence for gross anatomical abnormalities other than WMH were excluded. WMH were identified on axial T2 and FLAIR sequences by a board certified neuroradiologist. WMH were characterized via manual inspection and categorized according to the scale’s criteria. Results: 95 patients (36.1 %: mean age: 41.8) had no WMH on axial T2 and FLAIR imaging and 168 patients (63.9%, mean age: 51.4) had WMH. Of those with WMH, 94.1% (n=158) had lobar hyperintensities (frontal: 148/158, 93.7%; parietal: 57/158, 36.1%; temporal: 35/158, 22.1%; occipital: 9/158, 5.7%), 13/168, 7.7% had basal ganglia WMH, 49/168, 29.1% had periventricular WMH, and 17/168, 10.1% had infratentorial WMH. 101/168 patients (60.1%) had bilateral WMH and 67/168 (39.9%) had unilateral WMH (34 right hemisphere /33 left hemisphere). Discussion: Amongst ARMR participants who were enrolled from Mayo Clinic Arizona and who had clinical brain MRIs, nearly 2/3 had WMH. The WMH were most common in the frontal lobes. Describing the features of WMH in those with migraine and comparing them to WMH attributable to other etiologies might be useful for developing classifiers that differentiate between migraine-specific WMH and other causes of WMH.